Active vitamin D activates chondrocyte autophagy to reduce osteoarthritis via mediating the AMPK–mTOR signaling pathway - Kong, Chunyu; Wang, Changlei; Shi, Yuquan; Yan, Lei; Xu, Junhua; Qi, Wufang (Biochemistry and cell biology, 2020)
Osteoarthritis (OA) is a common joint degenerative disease. Vitamin D (VD) is essential for bone health. We hypothesized that active VD could be used as a therapeutic treatment for OA. Low serum levels of 25-hydroxyvitamin D [25(OH)D] have been found in patients with OA, and thus the serum level of VD could be diagnostic of OA. To test this, we established a mouse model of OA. The results from staining with hematoxylin–eosin and Safranin O – Fast Green indicated that active VD reduced the symptoms of OA in mice. The results from Western blotting indicated that treatment with VD increased the activity of the p-AMPK–AMPK signaling pathway and decreased the p-mTOR–mTOR pathway; it also increased the ratio of LC3II:LC3I antibodies and the protein expression levels of Beclin-1, but decreased the level of p62. Further, treatment with VD reduced the levels of tumor necrosis factor-α and interleukin-6 both in cartilage tissues and in chondrocytes. Administration of the AMPK inhibitor compound C and autophagy inhibitor 3-methyladenine (3-MA) reversed these changes following VD treatment. In addition, the results from transfection with mRFP-GFP-LC3 indicated that active VD led to autophagosome aggregation in OA chondrocytes. 3-MA inhibited cell autophagy and promoted inflammation in OA. This study provides evidence that active VD activate chondrocyte autophagy to reduce OA inflammation via activating the AMPK–mTOR signaling pathway. Treatment with active VD could be a novel therapeutic option for OA.